(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2025)
Social psychology has significant potential for elucidating tourism, as tourism intrinsically entails interactions among visitors, residents, and service personnel. The majority of tourism research based on social psychology originates from social cognition, which investigates the development, operation, and progression of cognitive processes within social contexts. Several important frameworks, such as attitude theory, the heuristic systematic model, the elaboration likelihood model, cognitive dissonance theory, and the theory of planned behavior, have been extensively utilized to elucidate tourist perceptions, decision-making, and behavior